2013
DOI: 10.1002/ppul.22968
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled corticosteroids and bone mineral density at school age: A follow‐up study after early childhood wheezing

Abstract: ICS use during childhood may be related to a decrease in BMD at late school age. It is important to use the lowest possible ICS dose that maintains adequate asthma control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 29 publications
2
14
1
1
Order By: Relevance
“…Rodriguez‐Martinez et al found that treating patients with recurrent wheezing or mild persistent asthma with daily inhaled corticosteroids results in higher gain in quality adjusted life years (QALY) compared to intermittent treatment . Sidoroff et al reported that regular inhaled corticosteroid use for longer than 6 months in children aged less than 6 years was associated with decreased bone mineral density in the lumbar spine; the amount of the cumulative dose until age 12 was correlated with the amount of decrease in femoral bone mineral density . Petsky et al studied asthmatic children randomized to use of fractional exhaled nitric oxide (FeNO) monitoring as a treatment guide, and found that use of FeNO was associated with decreased severe exacerbations.…”
Section: Asthmasupporting
confidence: 68%
See 1 more Smart Citation
“…Rodriguez‐Martinez et al found that treating patients with recurrent wheezing or mild persistent asthma with daily inhaled corticosteroids results in higher gain in quality adjusted life years (QALY) compared to intermittent treatment . Sidoroff et al reported that regular inhaled corticosteroid use for longer than 6 months in children aged less than 6 years was associated with decreased bone mineral density in the lumbar spine; the amount of the cumulative dose until age 12 was correlated with the amount of decrease in femoral bone mineral density . Petsky et al studied asthmatic children randomized to use of fractional exhaled nitric oxide (FeNO) monitoring as a treatment guide, and found that use of FeNO was associated with decreased severe exacerbations.…”
Section: Asthmasupporting
confidence: 68%
“…18 Sidoroff et al reported that regular inhaled corticosteroid use for longer than 6 months in children aged less than 6 years was associated with decreased bone mineral density in the lumbar spine; the amount of the cumulative dose until age 12 was correlated with the amount of decrease in femoral bone mineral density. 19 Petsky et al studied asthmatic children randomized to use of fractional exhaled nitric oxide (FeNO) monitoring as a treatment guide, and found that use of FeNO was associated with decreased severe exacerbations. However, the total dose of inhaled corticosteroids was higher in this group, and there was no effect on quality of life, lung function tests or control.…”
Section: Asthma Managementmentioning
confidence: 99%
“…Initiation of inhaled glucocorticoids at a young age has potential effects on bone accrual, peak bone mass and growth in addition to the cumulative lifetime effects of these medications. Of concern are recent studies in pediatric populations, which have demonstrated detrimental effects of these medications on bone growth and density [35, 37, 38]. …”
Section: Skeletal Effects Of Inhaled Glucocorticoids In Pediatric Astmentioning
confidence: 99%
“…In another study, children who received regular inhaled glucocorticoid treatment before 6 years of age, had significantly reduced BMD at the lumbar spine (mean aBMD=0.81, 95% CI 0.74–0.90) detected by late school age (median age 12.3 years) compared to those who had never used these medications. This analysis did not find a significant impact on BMD in the children with regular IGC use between 6 and 12 years of age, suggesting that exposure before 6 years of age may have the most critical impact [38]. …”
Section: Skeletal Effects Of Inhaled Glucocorticoids In Pediatric Astmentioning
confidence: 99%
“…The bone adapts to mechanical stress, largely changing the size and shape that are the main factors of resistance to fracture (Turner, 2006). Specific characteristics of the skeleton in different species of mammals are interdependent due to environmental, adaptive , physiological (Stynder, 2008;Coates et al, 2016), specific (McClure et al, 2001) indicators not only in animals but also in humans (Sidoroff et al, 2013).…”
Section: Introductionmentioning
confidence: 99%